1969
DOI: 10.1071/ch9692029
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of the roots of Desmodium gangeticum

Abstract: Previously, the occurrence of several simple indolic bases in the aerial portions of Desmodium gangeticum D.C. (Leguminosae : Papilionaceae) was reported by us.lSince the roots of this species find use in the ayurvedic system of medicine,= we have now investigated their alkaloidal constituents. The present communication describes the isolation and identification of seven alkaloids representing three structural types, viz. carboxylated and decarboxylated tryptamines, and ,B-phenylethylamine. The bases identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…These reactions, catalyzed by the aromatic amino acid decarboxylase (E.C.4.1.1.28), are commonly the first step in the biosynthesis of many important alkaloids (Berlin and Fecker, 2000;Facchini and DeLuca, 1995;Gu¨gler et al, 1988;Marques and Brodelius, 1988). b-Phenethylamine (b-PHA), the decarboxylated form of phenylalanine, has formerly been reported as the usual component of alkaloids in cactus (Keller et al, 1973;Mata and McLaughlin, 1980) and in perennial legume trees such as Alhagi pseudalhagi , Prosopis nigra (Moro et al, 1975), and many species of Desmodium (Ghosal and Banerjee, 1969;Ghosal et al, 1972;Ghosal and Mehta, 1974) and Acacia (Camp and Norvell, 1966;Fitzgerald, 1964). Tissue extracts of these plant species generally contain a variety of b-PHA derivatives (e.g., mescaline, N-methyl-b-PHA, and hordenine), often referred to as PHA alkaloids, which show sympatho-mimetic properties, psychic effects, and other versatile pharmacological actions on higher animals Kapadia and Fayez, 1970;Smith, 1977a).…”
Section: Introductionmentioning
confidence: 99%
“…These reactions, catalyzed by the aromatic amino acid decarboxylase (E.C.4.1.1.28), are commonly the first step in the biosynthesis of many important alkaloids (Berlin and Fecker, 2000;Facchini and DeLuca, 1995;Gu¨gler et al, 1988;Marques and Brodelius, 1988). b-Phenethylamine (b-PHA), the decarboxylated form of phenylalanine, has formerly been reported as the usual component of alkaloids in cactus (Keller et al, 1973;Mata and McLaughlin, 1980) and in perennial legume trees such as Alhagi pseudalhagi , Prosopis nigra (Moro et al, 1975), and many species of Desmodium (Ghosal and Banerjee, 1969;Ghosal et al, 1972;Ghosal and Mehta, 1974) and Acacia (Camp and Norvell, 1966;Fitzgerald, 1964). Tissue extracts of these plant species generally contain a variety of b-PHA derivatives (e.g., mescaline, N-methyl-b-PHA, and hordenine), often referred to as PHA alkaloids, which show sympatho-mimetic properties, psychic effects, and other versatile pharmacological actions on higher animals Kapadia and Fayez, 1970;Smith, 1977a).…”
Section: Introductionmentioning
confidence: 99%
“…Total alkaloids of this species showed smooth muscle stimulant, anticholinesterase, CNS stimulant and depressant responses (Ghosal and Bhattacharya, 1972). Chemical investigations have revealed that this plant contains alkaloids like tryptamines, phenethylamines, and their N-oxides (Ghosal and Banerjee, 1969); pterocarpanoids like gangetin, gangetinin, desmodin, and desmocarpin (Purushotaman et al, 1971(Purushotaman et al, , 1975Ingham and Dewick, 1984); phospholipids (Rastogi et al, 1971), sterols such as 24-ethylcholesta-5, 22-diene-3␤-ol; 24-ethylcholest-5-en-3␤-ol and 24-methylcholest-5-en-3␤-ol (Mukat and Varshney, 1986), flavone glycosides such as 4 ,5,7-trihydroxy-8-prenylflavone-4 -O-␣-l-rhamnopyranosyl-(1-6)-␤-d-glucopyranoside and 8-C-prenyl-5,7,5 -trimethoxy-3 ,4 -methylenedioxy flavone (Yadava and Reddy, 1998;Yadava and Tripathi, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…light petrol. The identity , of the alkaloids was established by co-TLC with authentic markers (GHOSAL and BANERJEE, 1969;GHOSAL et al, 1972;, by their chemical transformation into known compounds, where possible, and from correspondence of melting point,optical rotation, UV, PMR, and MS of the alkaloids and their derivatives with those reported in the literature (KAPADIA and FAYEZ, 1970;SPAIR et al, 1970;. T h e petrol.…”
Section: Methodsmentioning
confidence: 99%
“…It showed TLC behavior, colour reactions, and UV absorption maxima characteristic of N-methyltyramine (GHOSAL and BANERJEE, 1969). T h e minor component, from the aforementioned preparative layer chromatography, was obtained as a brown gum (11 mg).…”
Section: N-methyl-b-phenethylaminementioning
confidence: 99%